Phylogenomics reveals multiple introductions and early spread of SARS-CoV-2 into Peru - Juscamayta-López, E. (2021)
We are greatly grateful to all health personnel of Peru, especially to members of the Respiratory Virus Laboratory from NHI-Peru for their dedication in providing continued diagnostic and high-quality care during the pandemic. The authors would like to express our deep gratitude to Dr. Kelly Levano for his critical review of this manuscript. In addition, we wish to thank Guillermo Trujillo and members of the Respiratory Infectious Diseases Laboratory from NHI-Peru, especially Helen Horna and Liza Linares for their support for the Whole-Genome Sequencing. This work was supported by the National Institute of Health of Peru and the CONCYTEC-FONDECYT Program of Proyectos Especiales: Respuesta al COVID-19 2020-01-01 [grant number 034-2020-FONDECYT].